Effectiveness of Combined Treatment Using Physical Exercise and Ultrasound-Guided Radiofrequency Ablation of Genicular Nerves in Patients with Knee Osteoarthritis - Alessandro de Sire; Lorenzo Lippi; Claudio Curci; Dario Calafiore; Carlo Cisari; Antonio Ammendolia; Marco Invernizzi (Applied Sciences, 2021)
Radiofrequency (RF) is a mini-invasive neuromodulation intervention that is commonly used in chronic pain conditions including general musculoskeletal pain related to several diseases, including knee osteoarthritis (KOA). However, to date, few studies investigated synergistic therapeutic approaches combining RF with rehabilitative physical exercise protocols in KOA patients. This prospective cohort study aimed at assessing the short-term effects on pain in KOA patients of a multimodal intervention consisting of ultrasound (US)-guided RF geniculate ablation and concomitant rehabilitative physical exercise. We included grade III KOA patients with knee pain (Numerical Pain Rating Scale, NPRS >4) not responsive to conventional treatments. They underwent a combined intervention including US-guided RF geniculate ablation and a 2-week physical exercise program. At the baseline (T0) and 1 month after (T1) we assessed: NPRS, Knee Injury and Osteoarthritis Outcome Scale (KOOS), quality of life, exercise adherence, and safety. All the 47 KOA patients enrolled (68.8 ± 13.7 years old) showed a reduction of pain (NPRS: 7.48 ± 1.74; 3.63 ± 1.68; p < 0.001). In addition, there was a significant improvement (p < 0.05) also in the other functioning and HRQoL outcomes. Adherence to the exercise program was over 80% in more than half (28) of the patients. No major adverse events were reported. These findings suggested that US-guided RF ablation of genicular nerves combined with rehabilitative exercise therapy might be considered a safe and effective approach in the complex management of KOA patients.